Tinjauan Sistematis Pengelolaan Obat dan Vaksin di Dinas Kesehatan Kabupaten/Kota: Systematic Review of Drug and Vaccine Management at District/City Health Offices - Tashya Dhela Maylinda; Nanang Munif Yasin; Chairun Weidyaningsih (Jurnal Surya Medika (JSM), 2023)
The availability of drugs in healthcare facilities will ensure that people get the medicines they need. To ensure the availability of drugs in healthcare facilities, good drug management must be carried out. The drug management cycle includes the stages of selection, planning, procurement, storage, and distribution. This systematic review aims to identify and characterize research methods, guidelines, indicators, and delivery of results in the evaluation of drug and vaccine management in District/City Health Offices. This systematic review uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Search for articles using Google Scholar, limiting the management of drugs and vaccines carried out at District/City Health Offices which are published from 2017 to 2022. Articles that meet the criteria are evaluated for methods, guidelines, and data processing, and the management stages are evaluated. Article quality was assessed using a modified Downs and Black checklist. Search results using the Google Scholar database obtained 1435 articles. After checking the research location and the year the article was published, 1426 articles did not meet the inclusion criteria. Of the nine articles than one article entered the exclusion criteria because it was a literature review. The results of a systematic review show that qualitative methods are the most frequently used in evaluating drug management, but qualitative methods also have many weaknesses to cover these weaknesses, mixed method research can be carried out. Quantitative research obtained the results of the percentage of drug management accuracy against indicators and qualitative research was carried out to find problems through content analysis. It is hoped that combining these methods will result in more precise drug management evaluation results so that suggestions for improvement will be more targeted.